Estrategias de captación de clientes en el Ferricentro Frank del cantón Baba periodo 2022. - Pin Anchundia, Micheel Nathaly (2023)
The present research work was carried out at Ferricentro Frank, in Baba Canton, Los Ríos Province, within the market dedicated to the retail sale of hardware items. The objective of this study was to analyze the customer acquisition strategies applied in the company, evaluating the level of satisfaction and customer behavior to improve public recognition, which was linked to the line of research administrative, financial, tax, audit and control management that frames the sub-line of marketing and commercialization so there are activities such as guides that allow them to offer their products to the market in order to have income, given this will be taken as a recommendation in this document. The methodology used in the research is the descriptive method that described the variables and actions under study, through the evaluation techniques of internal and external factors, which allowed obtaining the following results: internally, the company is in a higher average of 2. 5 rating of the evaluation diagnosis, but it has internal weaknesses in which it needs to improve such as the experience and knowledge of the collaborators when selling a product, externally there are threats that should be taken more into consideration, thus concluding that the variables are divided into positive and negative, that is, good and bad, the level of satisfaction and behavior is average and the potential customer should be taken more into account.